Psychosocial impacts of fixed orthodontic treatment in Lahore, Pakistan - Shahzad, Hazik Bin; Iftikhar, Dalia; Huda, Noor ul; Enver, Nayha; Awais, Faiza; Hussain, Shabbir (UI Scholars Hub, 2020)
Background: The aim of this study is to assess psychosocial impacts on oral health-related quality of life between individuals currently undergoing orthodontic treatment and those who have completed treatment. Methods: A total of 135 individuals were selected from the Orthodontic Department at Rashid Latif Dental Hospital, Lahore, Pakistan. Current and previous orthodontic treatments were recorded. A questionnaire on oral impacts on daily performance was used to assess functional, psychological, and social limitations. Results: The most prevalent psychosocial impact was difficulty in smiling/laughing (26.6%). Logistic regression analysis showed that individuals currently undergoing orthodontic treatment are 2.9 times more likely to experience difficulty in eating compared with individuals with completed orthodontic treatments, and the difference between groups was significant (p < 0.001). Furthermore, difficulty speaking was 6.7 times more likely to occur in individuals currently undergoing orthodontic treatment than in individuals with completed orthodontic treatment; the difference between groups was also significant. Conclusion: Besides the normal and expected difficulties in eating, cleaning teeth, and speaking (i.e., functional impacts), individuals undergoing orthodontic treatment are prone to experience severe difficulties in smiling and going out. These issues are related to the psychosocial impacts and limitations of orthodontic treatment and demonstrate that the latter does not grant patients a higher status in society if they refrain from social settings and have difficulty smiling.